Prevalence and Characteristics of Chronic Pain in Buprenorphine and Methadone-Maintained Patients - Delorme, Jessica; Pennel, Lucie; Brousse, Georges; Daulouède, Jean-Pierre; Delile, Jean-Michel; Lack, Philippe; Gérard, Antoine; Dematteis, Maurice; Kabore, Jean-Luc; Authier, Nicolas; Chenaf, Chouki; , TOXIDOL Study group (Frontiers in Psychiatry, 2021)
Chronic pain and substance use disorders frequently co-occur. Indeed, chronic pain is highly prevalent, affecting 23-68% of patients receiving opioid agonist treatments(OAT) worldwide. The majority of available estimates come from American studies, but data are still lacking in Europe. We aim to provide European estimates of the prevalence of chronic pain in patients receiving OAT using French data, since France is the first European country in terms of number of patients with OAT. The secondary objectives were to characterize the features and management of chronic pain, as well identify associated risk factors. We conducted a multicenter, cross-sectional study, recruiting patients treated either with buprenorphine or methadone in 19 French addiction centers, from May to July 2016. All participants had to complete a semi-directed questionnaire that collected sociodemographic and medical data, pain characteristics, and licit or illicit drug consumption. In total, 509 patients were included. The prevalence of chronic pain was estimated at 33.2% (95% CI: 29.1-37.3). Compared to non-chronic pain patients, chronic pain patients were older (38.4 vs. 36.1 years, p=0.006), were more unemployed (66% vs. 52%, p=0.003), had more psychiatric comorbidities (50% vs. 39%, p=0.02), and split their OAT for pain management more frequently (24% vs. 7%, p=0.009). Pain intensity was moderate or severe in 75% of chronic pain patients. Among patients with chronic pain, 15.4% were not prescribed, and did not self-medicate with, any analgesic drugs, 52.1% were prescribed analgesics (non-opioid analgesics, 76.3%; codeine, tramadol, opium, 27.2%; and morphine, fentanyl, oxycodone, 11.8%), and 32.5% exclusively self-medicated with analgesics. Moreover, 20.1% of patients with chronic pain also used illicit drugs for pain relief. On multivariate analysis, variables that remained significantly associated with chronic pain were age (OR=1.03 [95% CI: 1.00-1.05], p=0.02), anxiety (OR=1.52 [1.15-2.02], p=0.003), and depression (OR=1.25 [1.00-1.55], p=0.05). Chronic pain is a highly prevalent condition in patients receiving OAT, and its appropriate management remains uncertain, since insufficient relief and frequent additional self-medications with analgesics or illicit drugs were reported by these patients. Increased awareness among caregivers is urgently needed regarding a systematic and careful assessment, along with an adequate management of chronic pain in patients receiving OAT.